Обґрунтування конструкції механізму пересування потужних технологічних машин - Крупко, І. В.; Krupko, I. V. (ТОВ "ТЕХНІЧНИЙ УНІВЕРСИТЕТ "МЕТІНВЕСТ ПОЛІТЕХНІКА", 2024)
Основними машинами, що забезпечують розроблення корисних копалин відкритим способом, є потужні екскаватори. На сучасних кар’єрних екскаваторах застосовують в основному гусеничні механізми пересування, які мають цілу низку недоліків, основним із яких є низька довговічність ведучих коліс. Водночас аналіз працездатності (відмов) екскаваторів-драглайнів показав, що найменше відмов (6–8%) у крокуючих механізмів пересування, що пояснюється простотою конструкції саме ходового обладнання. Тому постає актуальним питання про застосування крокуючого ходового обладнання на потужних екскаваторах – прямих механічних лопатах.Метою дослідження є обґрунтування раціональних конструкцій механізмів пересування для потужних технологічних машин. Для досягнення поставленої мети вирішуються завдання, пов’язані з тим, що треба провести порівняльний аналіз гусеничних і крокуючих механізмів пересування й обґрунтувати шляхи підвищення їхнього технічного рівня; виконати на фізичній моделі дослідження формування навантажень у структурі привода чотирьохопорного механізму за різних режимів роботи; за результатами теоретичних і експериментальних досліджень обґрунтувати раціональні параметри чотирьохопорного механізму пересування.

Based on the results of the analysis of existing designs and calculation methods, the main disadvantages of caterpillar mechanisms have been identified, which consist in the presence of a large number of rapidly wearing parts, as well as the expenditure of significant energy on friction of the support base against the ground in three-legged walking mechanisms. These disadvantages are eliminated in the four-legged walking mover, in which the movement process is provided by an eccentric drive with alternating movement of two pairs of support skis. To achieve the set goal, theoretical and experimental studies of a fundamentally new design of the movement mechanism in relation to single-bucket excavators were carried out, which allowed to establish the regularities of load formation in the eccentric drive, which have an oscillatory nature and obey the cosine law with a repeating half-period of change corresponding to the rotation of the eccentric at an angle α=180°. A mathematical model of the movement process of a four-legged walking mover has been developed and theoretically substantiated, which comprehensively takes into account the structure of the excavator, the design features of the mechanism, starting from the eccentric drive and to the interaction of support elements with the ground base. Based on the results of the research, a method for selecting rational parameters of a four-legged walking mechanism has been proposed and recommendations for the use of such mechanisms on excavators and mining machines weighing up to 400 tons have been developed.
Justification of the design of the movement mechanism of powerful technological machines
Keywords: технічний рівень; чотирьохопорний механізм крокування; рушій; екскаватор; фізична модель; technical level; four-legged walking mechanism; mover; excavator; physical model